Barns hållbarhetsfrågor i digitala och fysiska gränssnitt - transduktionskedja som ett didaktiskt verktyg - Cecilia Caiman; Susanne Kjällander; Eva Norén; Farzaneh Moinian (Dalarna university, 2023)
In this article, we show empirically how preschool childrens' creative, physical, and digital leaps, provide new perspectives concerning childrens' engagement in ecology related questions in the domain of Sustainability Education. The metamorphosis of insects is explored by children digitally, embodied and 'hands-on', and the children move through the digital and analogue interfaces. Childrens' embodied explorations through instant encounters with nature has an obvious place where the digital world and nature become intersected forming a whole. We introduce a transduction chain, a didactic design-theoretic analysis tool, which supports teachers and researchers to get to hold of childrens' digital and analogue meaning-making sign use. We draw attention to the preschool children's contribution in the area, which is made visible through transduction processes. We do not yet have the answers to the complex questions of sustainability, implying the need of all citizens' participation and contributions. In anthropocene, it is also important to strengthen agency processes by paying attention to children's own course of actions and proposals. In light of this study, preschool teachers need to provide rich opportunities where children can explore and process what is happening around them.